SPE Annual Technical Conference and Exhibition 2013
DOI: 10.2118/166313-ms
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Horizontal Well Placement Using Fuzzy Logic

Abstract: Estimated to have over 3.5 billion barrels of original oil in place, the 114 year old Kern River Oil Field was a sleeping giant until the late 1960's when steamflooding began and oil production ramped up from 19,000 to over 142,000 BOPD by the mid 1980's. Kern River Field is now in decline, but still produces over 70,000 BOPD, making it one of the largest onshore oil producers in the continental United States. In 2007 the field's cumulative production reached two billion barrels of heavy oil. With the introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…In the case of fuzzy logic which enables a formal record of imprecise natural language concepts there are a number of intermediate values determining the membership degree between the lack of membership (absolute false) and full membership (absolute true) [12]. Fuzzy logic has made it possible to realistically assess the location of new wells on the reservoir thanks to the extended approach to the description of reservoir rock parameters [10]. However, fuzzy logic is most often used in combination with other artificial intelligence methods.…”
Section: Application Of Artificial Intelligence Methods In the Oil Anmentioning
confidence: 99%
“…In the case of fuzzy logic which enables a formal record of imprecise natural language concepts there are a number of intermediate values determining the membership degree between the lack of membership (absolute false) and full membership (absolute true) [12]. Fuzzy logic has made it possible to realistically assess the location of new wells on the reservoir thanks to the extended approach to the description of reservoir rock parameters [10]. However, fuzzy logic is most often used in combination with other artificial intelligence methods.…”
Section: Application Of Artificial Intelligence Methods In the Oil Anmentioning
confidence: 99%
“…Infill drilling helps in the recovery of bypassed reserves and could be optimized if the inherent uncertainties in reservoir properties/geology are incorporated using fuzzy logic. Popa (2013) presented a case where they applied fuzzy logic model to horizontal well identification using a complex 3D full field earth model developed with data from more than 21,000 wells. He reported that the application of fuzzy logic for horizontal well identification maximized production outcome of the field.…”
Section: Applications Of Fuzzy Logic In Drilling and Completionmentioning
confidence: 99%
“…Elements of sets with degrees of membership functions are generally known as fuzzy sets. A membership function allows for the fuzzification of both input and output variables (Popa 2013). With fuzzy rules generated and alpha-cuts taken from membership function, sensitivity analysis of input values is carried out to generate a robust output response.…”
Section: Introductionmentioning
confidence: 99%
“…In helping prediction, one alternative is by using soft computing techniques such as neural networks and fuzzy logic [4]. Fuzzy logic is an approach that deals with uncertain information and some aggregate variables with the appropriate membership function [5]. Fuzzy logic is a scientific method [6].…”
Section: Introductionmentioning
confidence: 99%